High Relative Parasitic Fitness of G22 Derivatives is Associated with the Epidemic Potential of Wheat Stripe Rust in China - Bai, Bing Bing (Plant disease, 2018)
In total, 13 commercial wheat cultivars around China and four races of Puccinia striiformis f. sp. tritici (namely, CYR32, CYR33, G22-9, and G22-14) were employed for a test of relative parasitic fitness (RPF) using the drop method. The RPF values were measured, including the urediniospore germination rate, the latent period, the uredinial length, the uredinial density, the infection area, the sporulation intensity, the lesion expansion speed, and the sporulation period. The results indicated that the parameters of relative parasitic fitness of the four P. striiformis f. sp. tritici races on the 13 wheat cultivars were significantly different (P = 0.00) in sporulation intensity, lesion expansion speed, uredinial length, sporulation period, uredinial density, and latent period. The urediniospore germination rates of the four P. striiformis f. sp. tritici races for the test were significantly different (P = 0.00), whereas no correlation with the different cultivars was observed (P = 1.00). The infection areas of the tested races on the different cultivars were significantly different (P = 0.00) but there were no obvious manifestations among the various races (P = 0.20). Principal component analysis (PCA) showed that the sporulation intensity represented sporulation capacity and scalability, the latent period indicated infection ability, and the urediniospore germination rate represented urediniospore vigor, all of which fully contributed to the RPF in the interaction of the four races and 13 wheat cultivars, which was calculated by the following formula: RPF = (sporulation intensity × urediniospore germination rate)/latent period. The sporulation and infection of G22-9 on the 13 large-scale cultivated cultivars were the highest, and the RPF of G22-9 was higher than that of the predominant races, CYR32 and CYR33. This result suggested that G22-9 could become a new predominant race and potentially cause epidemics of wheat stripe rust in China. To prevent potential epidemics, susceptible wheat cultivars should be withdrawn from production and breeding programs should reduce the use of Yr10 and Yr26 and use other more effective resistance genes in combination with nonrace-specific resistance for developing wheat cultivars with durable resistance to stripe rust